ANALISIS STRATEGI TEKNOLOGI PLTS FOTOVOLTAIK DI INDONESIA TERHADAP NILAI EQIVALENSI DAN PEMANFAATAN PERWILAYAH - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The equivalence value and utilization by region in the focus of the Technology Strategy Analysis Photovoltaic solar power in Indonesia is a form of solar power energy potential optimization analysisbased on the results of the model output MARKAL by taking two cases: the base case (BASE CASE) and the case of investment costs vary PLTS (PVCOST). The base case is a case where all conditionsare taken based on the conditions from 2000 to 2016 when growth in electricity consumption is assumed to remain average, in 2030 Java is expected to require PLTS of 12.16 GW. But the use ofsolar power at 12.16 GW by-case basis and 46.65 GW in the case PVCOST in Java and 16.85 GW in the case PVCOST in Sumatra can be said to be irrational considering there are still local energysources that can be used like a mini/micro-hydro and geothermal has not been used optimally.